SUMBANGAN REMITENSI DALAM DUNIA PENDIDIKAN - Nur Isroatul Khusna (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2017)
ABSTRACT The aims of this study are to describe the allocation of remittance usage by the family of employee women (TKW) and to describe how much allocation of remittance usage for education. This research is descriptive research using survey method. The population in this study is the TKW who have family at school in the Dono Village Kecamatan Sendang who worked abroad and its amount about respondents. The sample which is taken all as many as 26 respondents because respondent under 100 person. Analysis of the data that is used single-tabulation analysis and percentage to obtain the general description of each variable. This research shows that evenly they post of remittance every mounth and utilization by family of remittences allocated to meet the needs of boards and all family give money of remittance for school pay between 5%-40% from all remittance their have. KEYWORDS: employee women, remittance ABSTRAK Tujuan penelitian ini adalah (1) mendeskripsikan alokasi penggunaan remitensi oleh keluarga tenaga kerja wanita (TKW), dan mendeskripsikan berapa alokasi penggunaan remitensi tersebut untuk pendidikan. Penelitian ini adalah penelitian deskriptif dengan metode survei. Populasi penelitian adalah TKW yang memiliki keluarga yang masih bersekolah di Desa Dono Kecamatan Sendang. Jumlah sampel sebanyak 26 karena jumlah seluruh responden kurang dari 100. Teknik analisis data menggunakan analisis tabulasi tunggal dan persentase untuk memperoleh deskripsi umum setiap variabel. Hasil penelitian menunjukkan bahwa alokasi remitensi untuk pendidikan sebanyak 5% - 40% dari seluruh remitensi yang dimiliki. KATA KUNCI: tenaga kerja wanita, remitensi